En jämförelse mellan två datorprogram för utbytesberäkningar - Samuelsson, Johan (2005)
This thesis is made on behalf of SCA's Forestry Division and is a comparison of two bucking simulation tools: Aptan (manufactured by Skogforsk) and Best/upr (from Berget Systemdesign). The data is based on 32 stands from SCA's forests in Norrbotten and Västerbotten. The objective is to compare the simulations created by the tools with the harvested volumes from those stands. Three variables are needed for the bucking simulation; these are the diameter distribution (at breast height), the relationship function between diameter and height, and the taper coefficients. The volumes of five different assortments from the stands are compared. The assortments are as follows: sawlogs from Scots pine (named TT), sawlogs from Norway spruce (GT), coniferous pulpwood (BM), hardwood pulpwood (LM) and the total volumes from each stand (TOT).